Error Analysis on Students' Business Letter Writing - Artika Wina Fitriani; Actinis Muqsitha Paradista (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2025)
Writing a business letter is a fundamental skill in the professional world, yet it presents various difficulties that can challenge even experienced writers. This research aims to analyze the common errors found in students’ business letter writing, categorize them, explore their possible causes, and suggest educational approaches to address these issues. This research used a descriptive quantitative approach. To achieve these objectives, frequencies, percentages and means of errors were calculated and tabulated. The data gathered by observation and documentation, where the documentation was writing assignment assigned by the lecturer. The result of research showed that students’ error in writing business letter were 55 errors. First, there were 29 errors in omission which were 52,7% of total errrors. Second, there were 19 errors in misformation which were 34,5% of total errors. Third, there were 6 error in addition which were 11% of total errors. There were 1 error in misordering which were 1,8% of total errors. Furthermore, the dominant errors in this research was omission which were 52,7% of total errors. In addition, brainstorming, drafting, peer review, and revising should be done as this improves error awareness and overall quality. Moreover, the teachers can assist the learners so that they will be able to draft business letters that are grammatically correct and contextually suitable.